A profile of eye-lid conditions requiring reconstruction among the patients attending an oculoplasty clinic in mid-western region of Nepal - Gautam, P; Adhikari, RK; Sharma, BR (Nepalese Journal of Ophthalmology, 2011)
Introduction: Some eyelid defects require reconstruction. Objective: To study the eyelid conditions requiring reconstruction among the patients attending an oculoplasty clinic of a tertiary level eye institute. Materials and methods: All the cases of eyelid reconstruction surgery of two years were retrospectively included in this study. The parameters studied were causes of eyelid defects, age and gender of the patients and the reconstructive surgical procedures. Results: Of 43 cases that required eyelid reconstructive surgery 17 (39.53 %) had ocular tumors and 16 (37.2%) had trauma. The mean age of presentation was 42 years ± 13.89 (4- 84 years. Of the eyelid tumors, benign lesions were found in 7 (41.1%) followed by basal cell carcinoma in 5 (29%). The surgical procedures carried out were direct closure of defects in 15 (35%), excision of cicatrized tissue with skin graft in 7 (16%), reconstruction with rotational flap in 6 (14%), blepharoplasty in 4 (9%), gold weight in 4 (9%), lid sharing procedure (Cutler-Beard procedure) in 3(7%), lateral tarsorraphy in 2 (5%) and canalicular repair with silastic tube intubation in 2 (5%). Conclusion: Ocular tumors are the most frequent conditions requiring eyelid reconstructive surgery. The common reconstructive procedures are direct closure followed by excision of cicatrized tissue with skin graft. Keywords: eyelid; Oculoplastic surgeries; trauma; tumor DOI: 10.3126/nepjoph.v3i1.4279 Nepal J Ophthalmol 2011;3(5):49-51